2019
DOI: 10.1111/head.13622
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Shift Work on Migraine: A Case Series and Narrative Review

Abstract: Objective We present a case report of 2 migraine patients engaged in shift work, followed by a narrative review, to assess whether shift work influences headache‐related disability and chronification of migraine. Background Numerous modifiable factors can lead to chronification of migraine and to higher headache‐related disability. These include, among others, obesity, depression, overuse of acute medications, ineffective acute treatments, and stressful life events. Sleep disruptions and disorders are also fel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 44 publications
4
34
0
1
Order By: Relevance
“…The question of job status was limited between semi-skilled worker versus university professor and laborer versus senior executive (30,36). A prospective study of two selected shift workers with chronic refractory migraine suggested an association between night shifts and work absences, but the sample size of two was too small to make definite conclusions (35).…”
Section: Resultsmentioning
confidence: 99%
“…The question of job status was limited between semi-skilled worker versus university professor and laborer versus senior executive (30,36). A prospective study of two selected shift workers with chronic refractory migraine suggested an association between night shifts and work absences, but the sample size of two was too small to make definite conclusions (35).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, in a recent case series study, Sandoe et al described two‐shift workers with severe migraine headache‐related disability, who suffered a worsening of their headache after beginning night shift work. Both improved when switched back to day shifts, and worsened coming back on night shifts.…”
Section: Resultsmentioning
confidence: 99%
“…On the other side, it may be important to adopt workplace preventive measures for migraine patients and consider the opportunity for more severe, chronic migraineurs, to modify work schedules that should be periodically re-assessed according to the migraine course and its transition to more or less disabling patterns. 40 Overall, some limitations of the review need to be considered for a suitable interpretation of the results. The low number of reviewed studies and the not homogeneous methodological approaches adopted, in terms of analyzed outcomes (ie, migraine prevalence, incidence or risk), heterogeneous populations investigated (ie, national working populations, healthcare workers, nurses), and different sample size prevent a suitable comparison of the obtained findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…given that previous studies report significant correlations between migraine-related disability and sleep disturbances 39 , and altering sleep (e.g. by switching back to day shifts from night shifts) can have a profound effect on migraine-related disability scores 40 . This may reflect the small number of studies and the high heterogeneity between them.…”
Section: Migraine Disabilitymentioning
confidence: 97%